Perhitungan Biaya Pembangunan Sistem Informasi Pariwisata Kota Sawahlunto Menggunakan Metode COCOMO II - Prasetya Muhamad Aditya; Aditya Rachmadi; Satrio Agung Wicaksono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Cost calculation is one of the decisive factors in making software. A small cost estimation will result in low quality produced software, otherwise a large cost estimation will result in a waste of expenditure. Both of these factors will potentially result in software project failure. There are several techniques and software cost estimation models that are classified into algorithmic and non algorithmic. Each has advantages and disadvantages, but there is no best techniques for all software development conditions. One of the most popular algorithmic methods for estimating software development costs is COCOMO II. COCOMO II proves to be a flexible model and has precise accuracy to use in cost estimates. Therefore, research conducted on the software house Jasa Web Malang uses COCOMO II method, especially post architecture submodel in estimating the cost of one of their projects. The goal is that this method can be accepted and applied to the software house. The result of this research is the estimated cost used by using COCOMO II method is smaller than the cost incurred by Jasa Web Malang and the cost estimation method using COCOMO II with post architecture submodel can be applied to software house Jasa Web Malang if the software house get flexible clients in waiting for the decision of the value of the system because to get the price of the System by calculating using COCOMO II method takes longer time than using guesstimate method.